Students’ Ability in Using Direct and Indirect Speech of English Department Students at Universitas Muslim Indonesia - Rosmiaty, Rosmiaty; Ratnawati, Ratnawati; Latukau, Hasni (ELT Worldwide: Journal of English Language Teaching, 2019)
In this study the writer wishes to know the students’ ability by the fourth semester students of Foreign Language Academy UMI in using direct and indirect speech. The whole population of this study was 160 students at fourth semester of Foreign Language Academy. There were 24 students out of 160 students to represent the population as the sample. The sample is taken by using random sampling technique. The types of the test consist of simple past tense, simple present tense and future tense. Through the data, the researcher obtained that 1 student or 4% were included in the highest score or having excellent level. 1 student or 4% were included in good level. Then, 2 students or 9% were included in sufficient level, 20 students or 83% were included in the low score or having fail level. The result revealed that there were still many underprivileged students in learning this subject.